The Role of Visual Arts in Developing Critical Thinking and Artistic Literacy in Secondary School Students - G‘aybullayeva Mehribon G‘olibovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the role of visual arts in fostering critical thinking and artistic literacy among secondary school students. Visual arts education develops students’ ability to analyze, evaluate, and create meaningful compositions, enhancing their aesthetic perception and problem-solving skills. The study discusses pedagogical strategies, including interactive teaching methods, project-based learning, and modern technologies, that support the development of students’ creative competencies. Research by Shovdirov S. A. and other scholars forms the theoretical foundation of the study.